2013
DOI: 10.1177/1525822x13500120
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship among Prepaid Token Incentives, Response Rates, and Nonresponse Bias in a Web Survey

Abstract: Few studies have employed a controlled experimental design to test the effectiveness of unconditional cash incentives on the rates of participation in web surveys. Even fewer studies have looked at the effects of these incentives on nonresponse bias in web surveys. This article addresses these two underresearched areas by utilizing two separate sources of data on a random sample of college students. Specifically, we examine the impact of prepaid token incentives on response rates to a web survey and compare su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 30 publications
3
20
0
Order By: Relevance
“…This improvement likely indicates that the incentive has higher leverage among college students who are normally unlikely to respond, such as off-campus students and men. This is a key finding given that some prior studies of college students have found that increasing the response rate through prepaid and lottery incentives may further bias responses in web surveys towards certain groups (Boulianne 2013;Heerwegh 2006;Laguilles et al 2011;Parsons and Manierre 2013). Contrary to prior studies, these data suggest that a five-dollar conditional incentive may increase representativeness while also improving response.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This improvement likely indicates that the incentive has higher leverage among college students who are normally unlikely to respond, such as off-campus students and men. This is a key finding given that some prior studies of college students have found that increasing the response rate through prepaid and lottery incentives may further bias responses in web surveys towards certain groups (Boulianne 2013;Heerwegh 2006;Laguilles et al 2011;Parsons and Manierre 2013). Contrary to prior studies, these data suggest that a five-dollar conditional incentive may increase representativeness while also improving response.…”
Section: Discussionmentioning
confidence: 53%
“…Two studies have found that lottery incentives attract female respondents to web surveys disproportionately (Heerwegh 2006;Laguilles et al 2011). A similar result was found for prepaid incentives and online surveys, with a group receiving a two-dollar prepaid incentive being less reflective of administrative records than the control group, with the control group matching official records for gender, but the incentivized group being overly female (Parsons and Manierre 2013). Some research also suggests that the gender gap is more pronounced with smaller dollar figures but still exists with higher values nonetheless (Boulianne 2013).…”
Section: Introductionmentioning
confidence: 65%
“…Furthermore, future studies should investigate diverse sizes of facilities and staff, which also have a wide range of male to female correctional officer ratios. Lastly, while overall response rates could be increased with incentives for participation, prior research has cited that incentives may introduce bias (Parsons and Manierre 2014). Finally, perceptions of promotional bias might be influenced by perceptions of hiring bias.…”
Section: Limitations and Future Researchmentioning
confidence: 95%
“…They conclude that "more research is needed on how monetary incentives can reduce nonresponse bias rather than merely raising the rate of response" (413). Parsons and Manierre (2014) in turn find that prepaid cash incentives may actually produce results that are less representative of the target population. In a metastudy, Singer and Ye (2013) report that most studies find no or only small effects on sample compositions and call for additional research on the subject.…”
Section: Effects On Sample Composition and Response Qualitymentioning
confidence: 99%
“…However, they do not find increased response rates in the 20 Euro and 50 Euro designs compared to those seen at the 10 Euro level. Finally, Parsons and Manierre (2014) report that the use of unconditional incentives improved response rates in a web survey based on a random sample of college students.…”
Section: Effects On Response Ratesmentioning
confidence: 99%